Redescription of the coral reef inhabiting axiidean shrimp Parascytoleptus tridens (Rathbun, 1906) (Decapoda: Calocarididae), and description of a new species from the south-western Indian Ocean - Komai, Tomoyuki; Anker, Arthur (Zootaxa, 2026)
The calocaridid shrimp genus Parascytoleptus Sakai & de Saint Laurent, 1989 was hitherto represented by two species, P. tridens (Rathbun, 1906), the type species, and P. papua Poore & Collins, 2010. Parascytoleptus tridens (Rathbun, 1906) was seen as a widespread Indo-West Pacific species, inhabiting shallow and moderately deep coral reefs. However, morphological comparisons and genetic analyses using two mitochondrial markers (COI and 16S rRNA genes) of material from various Indo-West Pacific localities revealed the presence of an undescribed species in the south-western Indian Ocean. In the present study, P. tridens is redescribed based on material from Hawaii, including the holotype, as well as specimens from French Polynesia and eastern Australia, whereas P. cognatus sp. nov. is described based on specimens from Nosy Iranja in the vicinity of Nosy Bé, Madagascar, and Réunion. The new species is characterised by the less developed rostrum, less pronounced lateral spines of the telson in the female, the proportionally wider cheliped meri, and the more extensive brownish markings on the cheliped palm and fingers. All three species of Parascytoleptus exhibit a strong sexual dimorphism in several morphological characters, including the shape of the carapace and its frontal region, size of the pleon, and proportions of the chelipeds.